Viscoelastic Material as Energy Dissipater Viscoelastic Damper for Building Structures to Mitigate the Seismic Vibration - Sarwar, Waseem (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The supplemental energy dissipation system is a practical approach to attenuate the structural response under extreme loading. Viscoelastic damping used to reinforce the structure against the seismic vibration, Viscoelastic material (VEM) most commonly used in viscoelastic dampers (VEDs). In this paper, dynamic mechanical analysis (DMA) approach is used to investigate the performance index of VEM.
Keywords: viscoelastic material; viscoelastic damper; dynamic mechanical analysis; dynamic properties; seismic control; materiał lepkosprężysty; tłumik lepkosprężysty; dynamiczna analiza mechaniczna; właściwości dynamiczne; kontrola sejsmiczna